Contributing to the GEO Model Web implementation: A brokering service for business processes. (October 2016) - Santoro, Mattia; Nativi, Stefano; Mazzetti, Paolo
Abstract: In the Earth system science domain, most current digital infrastructures are able to support data access rather than provide answers to complex questions – noticeably, supporting the ability to address the what-if questions posed by users. To this purpose, integrated modeling is an indispensable element. This work follows a recognizable gap characterized by high-level steps towards model integration: the Science-to-Information Technology barrier. This manuscript introduces an innovative approach to address such a gap in the "Model Web" framework initiative promoted by GEO (Group on Earth Observation) on its GEOSS (Global Earth Observation System of Systems) program. The methodological approach consists of five technologically neutral steps to build executable workflows from abstract business processes. A high-level architecture, based on the brokering pattern, is introduced to implement the proposed approach. By extending the GEOSS brokering framework, a proof-of-concept implementation is presented, argued, and ultimately experimentations and conclusions are discussed. Highlights: Innovative approach to build executable workflows from abstract business processes. Broker-based architecture for business process transformation. Proof-of-concept Business Process Broker implementation. Advance the GEO Model Web implementation.